A Thermodynamic Pathway Leading to Rapid Intensification of Tropical Cyclones in Shear - Chen, Xiaomin; Zhang, Jun A.; Marks, Frank D. (Geophysical research letters, 2019)
Understanding physical processes leading to rapid intensification (RI) of tropical cyclones (TCs) under environmental vertical wind shear is key to improving TC intensity forecasts. This study analyzes the thermodynamic processes that help saturate the TC inner core before RI onset using a column‐integrated moist static energy (MSE) framework. Results indicate that the nearly saturated inner core in the lower‐middle troposphere is achieved by an increase in the column‐integrated MSE, as column water vapor accumulates while the mean column temperature cools. The sign of the column‐integrated MSE tendency depends on the competition between surface enthalpy fluxes, radiation, and vertical wind shear‐induced ventilation effect. The reduction of ventilation above the boundary layer due to vertical alignment is crucial to accumulate the energy within the inner core region. A comparison of the RI simulation with a null simulation further highlights the impact of vortex structure on the thermodynamic state adjustment and TC intensification. Plain Language Summary A dry environment is unfavorable for tropical cyclones' development and intensification. Enhanced evaporative cooling from convective downdrafts in the dry environment reduces the temperature and humidity in the low‐level region of tropical cyclones, which in turn reduces the number and strength of the buoyant convective updrafts in the inner core of the storm. Under environmental vertical wind shear (i.e., wind speed and/or direction varying with height), the core of a tropical cyclone is tilted, allowing dry air intrusion into tropical cyclone circulation at lower levels. Understanding how the tropical cyclones can overcome the negative impacts of downdraft cooling is crucial to improve the intensity forecast using numerical weather prediction models, particularly the timing of rapid intensification onset. This study presents a potentially important thermodynamic pathway leading to the formation of a nearly saturated inner core of a tropical cyclone preceding rapid intensification, which is in connection with vertical alignment of the storm center at different vertical levels. Key Points The nearly saturated lower‐middle troposphere in the inner core region precedes the tropical cyclone (TC) rapid intensification in shear The moistening of the inner core region is achieved by a competition between surface heat fluxes, radiation, and ventilation effects Vortex alignment benefits the moistening of the TC inner core by reducing ventilation effect